What Linguistic Features Shape Literature Review Sections? An Analysis of Social Sciences Master’s Theses from a State University in the Philippines - Sumayo, Gideon Sindad; Tulud, Donnie Marasigan (Pascasarjana Universitas Negeri Makassar, 2025)
This research investigates the linguistic features shaping literature review sections in social sciences master’s theses from a state university in the Philippines. Employing a qualitative descriptive research design, it analyzed the lexico-grammatical features in 30 unpublished MA theses. Findings reveal the noticeable use of cohesion devices, such as anaphoric references and conjunctions, and lexical cohesion achieved through repetition. Reporting verbs were strategically used to give attributions to the borrowed ideas and assert writer stances, while hedges conveyed caution and boosters added conviction. Active and passive voices were applied to achieve clarity and depersonalization, respectively. Verbals, including gerunds, participles, and infinitives, were used to frame ideas and maintain coherence. These current findings accentuate the critical role of linguistic features in constructing coherent, impactful academic texts, such as literature reviews. The study provides insights to enhance graduate students’ writing skills, contributing to improved academic writing practices.